The Indonesian Council Ulama (MUI) and Religious Discourse In Indonesia - Achmad, Mukhsin (Tebuireng: Journal of Islamic Studies and Society, 2022)
This paper wants to explore the existence and role of the Indonesian Ulema Council (MUI) in religious discourse and practice in Indonesia. This research is library research using the theory of Critical Discourse Analysis by Norman Fairclough. The approach of this research is the political approach of Islamic law in Indonesia. Results This study found research findings related to the existence and role of MUI in the process of forming Islamic discourse in Indonesia. The MUI was designed by the government of the New Order Era as a medium of communication between the government and the ulama. The position of MUI in this era is more dominant in its role as "khodimul Hukumah" (government servant) and in the reform order its role has shifted to "khodimul ummah" (servant of the ummah). MUI as a big umbrella for Muslims has played a big role in shaping religious discourse in Indonesia through its products, namely fatwas and non-fatwas. Among the non-fatwa are in the form of tawsiyah, Tadzkiroh, amanah, attitude statements and appeals. Even though the fatwa and non-fatwa are morally binding, politically legal products of MUI products are often accommodated by the government into a legally binding public policy (law). In this context, the MUI has had an influence in the formation of religious discourse through the process of transformation from religious authority to state authority through government public policies.More about this source textSource text required for additional translation informationSend feedbackSide panels